The effect of organizational culture in the organizational commitment towards the development of talent management strategy in the business process outsourcing (BPO) industry / Neil T. Awit and Ramon M. Marticio - Awit, Neil T.; Marticio, Ramon M. (Universiti Teknologi MARA Kelantan, 2020)
This study examined the effect of Organizational Culture in the Organizational Commitment of the 298 rank and file employees from the BPOs within the Bonifacio Global City (BGC) and Makati Central Business District. The mixed-method approach was applied in this study which means that both quantitative and qualitative research methods were utilized. On the quantitative approach, the researchers adopted Allen and Meyer’s ThreeComponent Model (TCM) questionnaires in the assessment of the Organizational Commitment while the Cameron and Quinn’s Organizational Culture Assessment Index (OCAI) was utilized in the examination of the Organizational Culture. On the qualitative approach, the researchers constructed structured interview questions as a supplementary to the quantitative results, gauging both the Organizational Culture and Organizational Commitment. Results showed that 70.8% of the respondents belong to the youngest age group of 18 to 25 years old. OCAI revealed that the most prevalent Organizational Culture stood in between the Market and Adhocracy.Meanwhile, the respondents’ Affective Commitment varies on the age group. Specifically, those in between 31 to 35 years old exhibited the highest Affective Commitment. Furthermore, respondents with 1-5 years length of stay showed the highest Affective Commitment. Among the three forms of Organizational Commitment, Continuance was found to be the most prevalent among the respondents. Given the results, the two null hypotheses stated were rejected, concluding that the Organizational Culture has a significant effect on the Organizational Commitment, and; there is a significant difference between the demographic profiles of the respondents in terms of the Organizational Commitment.